PENGARUH AKUNTANSI MANAJEMEN TERHADAP EFISIENSI ANGGARAN BIAYA DAN PRODUKTIVITAS PADA AQUA HOME SERVICE DI KABUPATEN BOGOR - Muliadi, Dedi; Leman, Wahyu (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study aims to analyze the influence of the application of management accounting on cost budget efficiency and productivity in Aqua Home Service in Bogor Regency. In the face of increasingly fierce business competition, cost budget efficiency and productivity have become crucial issues for companies, especially for small and medium businesses such as Aqua Home Service. The implementation of effective management accounting is expected to help companies manage costs more efficiently and increase work productivity. The method used in this study is a quantitative approach with a survey technique. Data was collected through a questionnaire distributed to 30 respondents, consisting of managers and staff at Aqua Home Service. The data analysis technique uses simple linear regression to measure the relationship between the application of management accounting and budget efficiency, cost, and productivity. The results show that there is a positive and significant influence between the application of management accounting on the efficiency of the cost budget, with a regression coefficient value of 0.70, which shows that the application of management accounting can reduce unnecessary expenses. In addition, management accounting also has a positive effect on the company's productivity, with a regression coefficient of 0.65. Based on these results, it can be concluded that the application of management accounting has an important role in improving the efficiency of the cost budget and productivity of Aqua Home Service in Bogor Regency.